Aerobically digested sludge conditioning by Fe2+/citrate chelated-Fe2+ activated peroxymonosulfate oxidation - Liu, Changgeng; Chen, Xiao’e; Cai, Hongtu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Fe2+-Cit-PMS was more efficient for improving AeDS dewaterability than Fe2+-PMS.•Citrate introduction strengthened PMS activation in the presence of Fe2+.•Dosages of Fe2+, PMS, and citrate in Fe2+-Cit-PMS system were optimized.•Release of EPS bound water led to the enhanced AeDS dewaterability.•Fe2+-Cit-PMS and Fe2+-PMS were both helpful to improve HMs stabilization. This work investigated the dewatering efficiency of aerobically digested sludge (AeDS) conditioned by peroxymonosulfate (PMS) activation using Fe2+ and citrate chelated-Fe2+ (Fe2+-Cit) as activators. The results showed that compared to Fe2+-PMS oxidation, Fe2+-Cit-PMS oxidation was more capable of improving AeDS dewaterability because of the strengthened activation of PMS by Fe2+-Cit. Under the optimal conditions (PMS = 0.9 mmol/g volatile solids (VS), Fe2+ = 0.6 mmol/g VS, and citrate = 0.3 mmol/g VS), capillary suction time reduction, water content of sludge cake, and centrifuged weight reduction were 88.3%, 67.2%, and 39.7%, respectively. The contributions of sulfate radical, hydroxyl radical, and iron ions to the enhanced AeDS dewaterability were in the sequence of sulfate radical > hydroxyl radical > iron ions. The enhanced AeDS dewaterability was mainly contributed from the efficient decomposition of tightly bound extracellular polymeric substances and the neutralization of negative surface charge. Through the addition of citrate, the primary iron species in the liquid phase of AeDS was converted from Fe2+ in Fe2+-PMS system into Fe3+ in Fe2+-Cit-PMS system. Additionally, this work demonstrated that Fe2+-PMS oxidation and Fe2+-Cit-PMS oxidation were both helpful to improve the stabilization of heavy metals in AeDS.